Operational activities of ground service in Biman Bangladesh Airlines Ltd. - Yousuf, Nayeem Ibn (BRAC Univeristy, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Masters of Business Administration, 2017.